Reaction fronts in inclined tubes under a Poiseuille flow - Rivadeneira Vizcardo, Rodrigo Miguel (2022)
Reaction fronts of chemical activity propagate with velocities that depend on the angle of inclination of the container. Buoyancy forces due to changes in chemical composition across the front will affect the velocity and shape of the front. If an external Poiseuille flow is imposed, the conditions of propagation would also change depending on the strength of this flow. Fronts in vertical tubes can change from flat to nonaxisymmetric, and then to axisymmetric as the density gradient is increased. Imposing a Poiseuille flow or tilting the tube changes how this sequence takes place. In this paper, we study the combined effects of convection and forced Poiseuille flow in inclined tubes, solving numerically the reaction-diffusion equations coupled to the Navier- Stokes equations.